Comparative analysis of the degree of patient satisfaction after breast-conserving surgery with or without oncoplastic surgery: systematic review and meta-analysis - Lisboa, Fabiana Christina Araújo Pereira; Giorgi, Lucimara Priscila Campos Veras; Figueiredo, Ana Claudia Morais Godoy; Paulinelli, Régis Resende; de Sousa, João Batista (Frontiers in Surgery, 2024)
Introduction: Conservative surgery is the gold standard for the treatment of single and small tumors and, combined with the concept of oncoplastic tumors, brings good aesthetic results while maintaining cancer safety. The objective was to comparatively analyze the degree of satisfaction of patients undergoing breast conserving surgery (BCS), with and without oncoplastic surgery (OPS) using level II OPS techniques.Methods: Review with a search in the databases MEDLINE (by PubMed), EMBASE, Clinical Trials, Scopus, Web of Science, BVS and Oppen gray. The meta-analysis of random effects was performed using the Der Simonian-Laird method considering the odds ratio (OR) with a 95% confidence interval (95% CI).Results: There was no statistically significant difference in the aesthetic outcome between women who underwent OPS and BCS (OR 0.90; 95% CI 0.62 -1.30). The staging (OR 1.93; 95% CI 0.97 -3.84; I 2 = 15.83%); tumor location [central (OR 1.28; 95% CI 0.06 -27.49; I 2 = 17.63%); lower (OR 0.75; 95% CI 0.21 -2.65; I 2 = 2.21%); superior (OR 0.67; 95% CI 0.26 -1.74; I 2 = 0.00%] and tumor size (OR 8.73;; I 2 = 93.18%) showed no association with the type of BCS performed, with or without OPS. The degree of satisfaction remains even in cases of extreme oncoplasty.The level of patient satisfaction in relation to BCS was similar to that of the group undergoing OPS, highlighting that OPS allows the patient's satisfaction rate to be maintained even in the case of large or multicentric tumors.